Optimalisasi Strategi Komunikasi Pemasaran Perusahaan Startup PT. Tala Bumi Group dalam Bisnis Franchise Food and Beverages - Amelia, Nabila Syifa; Yudhistira, Nurfian (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to optimize the marketing communication strategy employed by PT. Tala Bumi Group, a startup in the food and beverage (F&B) franchise industry. This sector has been experiencing rapid growth in Indonesia, driven by a rising population and increased market demand. However, the coffee shop segment faces significant challenges due to heightened competition. This research utilizes a descriptive qualitative method with a case study approach, involving in-depth interviews with stakeholders and secondary data analysis to explore the 7P marketing mix components: Product, Price, Place, Promotion, People, Process, and Physical Evidence. The main findings indicate that PT. Tala Bumi Group successfully leverages digital communication—particularly through social media—to enhance brand visibility and market reach. In terms of the 7P strategy, the company has differentiated its product offerings and strengthened promotional activities, including influencer partnerships aimed at appealing to younger demographics. However, further optimization is needed in pricing strategy to align with shifting consumer behavior, as well as in customer loyalty initiatives to remain competitive. Enhancements in customer service processes and physical elements (e.g., store design) also emerged as key areas of focus. These findings contribute to the F&B franchise industry by providing strategic insights adaptable to dynamic market demands and competitive pressures.